Nationwide Results on Chronic Pain After Bilateral Transabdominal Preperitoneal Inguinal Hernia Repair. (December 2020) - Johansen, N.; Vyrdal, C. D.; Bisgaard, T.
Background: Majority of studies on chronic postoperative inguinal pain has described the occurrence after unilateral inguinal hernia repair. Endo-laparoscopic repair, for example, laparoscopic transabdominal preperitoneal inguinal hernia repair, has been recommended for primary bilateral symptomatic inguinal hernias, although the literature on chronic postoperative inguinal pain among this type of patients is limited. The present study analyzed chronic postoperative inguinal pain following bilateral transabdominal preperitoneal inguinal hernia repair. Methods: Nationwide consecutive patients who underwent bilateral transabdominal preperitoneal inguinal hernia repair (July 2012–June 2013) were recruited from the Danish Inguinal Hernia Database and cross-checked with hospital files and the National Patient Registry. A prospective follow-up was performed with a standardized postal questionnaire including questions on functional performance status assessed by a modified version of the Activity Assessment Scale. The primary outcome was incidence of chronic postoperative inguinal pain defined as moderate to severe pain-related impairment of everyday activities. Pain was registered according to the two individual groin areas. Furthermore, the overall incidence of chronic postoperative inguinal pain per operated inguinal hernia was calculated. Intensity of experienced pain (Activity Assessment Scale score) was compared between patients reporting pain from one versus both groin areas. Results: In total, 209 patients (418 hernia repairs) were analyzed (questionnaire response rate 83%). The median follow-up time was 27 months (22–34 months). In total, 27 of 209 patients (13%) complained of chronic postoperative inguinal pain from either one ( n  = 17) or both ( n  = 10) groin areas after bilateral transabdominal preperitoneal inguinal hernia repair. The incidence of chronic inguinal pain per operated hernia was 9%. The intensity of impairment due to pain (Activity Assessment Scale score) did not differ significantly between patients with chronic postoperative inguinal pain in one (19%) versus both sides (30%), p  = 0.056. Conclusion: Bilateral transabdominal preperitoneal inguinal hernia repair for symptomatic inguinal hernias was related to a high incidence (13%) of chronic postoperative inguinal pain and decreased functional performance status.